What Role Does Microthrombosis Play in Long COVID? - Iba, Toshiaki; Connors, Jean M.; Levy, Jerrold H. (Seminars in Thrombosis and Hemostasis, 2023)
Soon after the outbreak of coronavirus disease 2019 (COVID-19), unexplained sustained fatigue, cognitive disturbance, and muscle ache/weakness were reported in patients who had recovered from acute COVID-19 infection. This abnormal condition has been recognized as “long COVID (postacute sequelae of COVID-19 [PASC])” with a prevalence estimated to be from 10 to 20% of convalescent patients. Although the pathophysiology of PASC has been studied, the exact mechanism remains obscure. Microclots in circulation can represent one of the possible causes of PASC. Although hypercoagulability and thrombosis are critical mechanisms of acute COVID-19, recent studies have reported that thromboinflammation continues in some patients, even after the virus has cleared. Viral spike proteins and RNA can be detected months after patients have recovered, findings that may be responsible for persistent thromboinflammation and the development of microclots. Despite this theory, long-term results of anticoagulation, antiplatelet therapy, and vascular endothelial protection are inconsistent, and could not always show beneficial treatment effects. In summary, PASC reflects a heterogeneous condition, and microclots cannot explain all the presenting symptoms. After clarification of the pathomechanisms of each symptom, a symptom- or biomarker-based stratified approach should be considered for future studies.
Keywords: long COVID-19; microclots; SARS-CoV-2 spike protein; coagulation; platelets